Influence of Rice Husk Ash Particles on Microstructure and Mechanical Properties of AA7075-T6 Aluminium Matrix Composites Produced using Friction Stir Processing. - Mustafa Kamal, Amar Safwan (IRC, 2018)

(untitled)
As to reduce the production cost of AMCs, researchers found that RHA have potential to become reinforcement for the aluminium. Therefore, to prove the research, this project will run the experiments to verify it. Simply, the methodology for this project is to compare the microstructure (distribution of reinforcement in aluminium) and mechanical properties (microhardness and tensile strength) between aluminium alloy and AMCs reinforced with RHA particles. The factor that will change is the deposition method of the RHA. As the other parameters will be constant, therefore, previous research paper will be references to determine the values or types of parameters is the best to have better microstructure and mechanical properties. After the samples undergo the FSP, the microhardness will be tested using Vickers hardness test and tensile strength will be tested using Universal Testing Machine (UTM). For microstructure, scanning electron microscope (SEM) will be used to observe the distribution of reinforcement after FSP. From the results, AA7075/RHA-AMCs was successful produced using FSP. Three test were conducted and analysed which are microstructural observation, microhardness test and tensile test.